THE INVESTMENT POTENTIAL OF COMMERCIAL BANKS AND ITS ROLE IN ECONOMIC GROWTH (American Journal of Business Management, Economics and Banking, 2026)
This article examines the investment potential of commercial banks and its role in ensuring sustainable economic growth. Commercial banks are among the most important financial institutions in the economy, as they mobilize savings, transform them into investment resources, and allocate capital to productive sectors. The study analyzes the influence of capital adequacy, credit portfolio growth, asset quality, profitability, liquidity, and digital banking development on the investment capacity of commercial banks.The research is based on the IMRAD structure and applies descriptive statistical analysis, comparative analysis, trend analysis, and CAMELS-based evaluation. The results show that the strengthening of capital adequacy, expansion of credit portfolios, reduction of non-performing loans, improvement of profitability indicators, and rapid development of digital banking services increase the role of commercial banks as drivers of economic growth. The study concludes that the investment potential of commercial banks is an important factor in capital accumulation, financial intermediation, private sector development, and long-term macroeconomic stability.